Economic valuation of the ecosystem services of the Mesoamerican Reef, and the allocation and distribution of these values - Itziar Ruiz de Gauna; Anil Markandya; Laura Onofri; Francisco Gre\~no; Javier Warman; Norma Arce; Alejandra Navarrete; Marisol Rivera; Rebeca Kobelkowsky; Mayela Vargas; Marisol Hernández (Inter-American Development Bank (IDB), 2021)
Coral reefs are one of the most diverse and valuable ecosystems on Earth. The Mesoamerican Reef contains the largest barrier reef in the Western Hemisphere. However, its health is threatened, so there is a need for a management and sustainable conservation. Key to this is knowing the economic value of the ecosystem. 'Mainstreaming the value of natural capital into policy decision-making is vital' The value of environmental and natural resources reflects what society is willing to pay for a good or service or to conserve natural resources. Conventional economic approaches tended to view value only in terms of the willingness to pay for raw materials and physical products generated for human production and consumption (e.g. fish, mining materials, pharmaceutical products, etc.). As recognition of the potential negative impacts of human activity on the environment became more widespread, economists began to understand that people might also be willing to pay for other reasons beyond the own current use of the service (e.g. to protect coral reefs from degradation or to know that coral reefs will remain intact in the future). As a result of this debate, Total Economic Value (TEV) became the most widely used and commonly accepted framework for classifying economic benefits of ecosystems and for trying to integrate them into decision-making. This report estimates the economic value of the following goods and services provided by the MAR's coral reefs: USE VALUES Tourism & Recreation, Fisheries, Shoreline protection NON-USE VALUES To our knowledge, the inclusion of non-use values in the economic valuation of the Mesoamerican Barrier Reef System is novel, which makes the study more comprehensive.
Keywords: 330